Analysis of brain‐derived blood exosomes for diagnostics of synucleinopathies. (31st December 2021) - Dutta, Suman; Hornung, Simon; Kruayatidee, Adira; Maina, Katherine M; del Rosario, Irish; Paul, Kimberly; Poon, Wayne W.; Fogel, Brent L.; Bronstein, Jeff M.; Ritz, Beate; Bitan, Gal
Abstract: Background: Synucleinopathies are diseases characterized by aggregation and deposition of α‐synuclein in different brain cells. Diagnosis of these neurological disorders is challenging due to overlapping complex clinical symptoms. Developing reliable biomarkers that can distinguish among the synucleinopathies is an urgent public health need. Recently, α‐synuclein was shown to transfer via exosomes between different brain cells suggesting that measuring α‐synuclein in brain‐derived exosomes could serve as a potential biomarker for synucleinopathies. Method: In this study, we used antibody‐coated magnetic beads to immunochemically isolate specific exosomes released by neurons or oligodendrocytes from serum/plasma of healthy individuals and patients with Parkinson's disease and Multiple System Atrophy and measured biomarker concentration in them by a sensitive electro‐chemiluminescence ELISA. Oligodendroglial and neuronal exosomes were isolated from serum of 101 patients with MSA, 104 patients with PD and 100 healthy controls. Result: Significantly higher concentrations of α‐synuclein were found in both neuronal and oligodendroglial exosomes from patients than in controls. The absolute values of α‐synuclein in neuronal and oligodendroglial exosomes provided moderate separation between the MSA and PD groups, yet the ratio between the two cell types allowed separating the two disease groups with 90.0% sensitivity and 90.0% specificity. Conclusion: α‐Synuclein in brain‐derived blood exosomes provides a sensitive biomarker for distinguishing patients with MSA from healthy controls and from patients with PD using a blood test and suggest that the method can be expanded further for other neurodegenerative diseases.